THE PRODUCTION OF ANTI-Dirofilaria immitis ANTIBODIES FOR THE DIAGNOSIS DEVELOPMENT OF DIROFILARIASIS IN DOGS - Erawan, I Gusti Made Krisna; Tjahajati, Ida; Nurcahyo, Wisnu; Asmara, Widya (Buletin Veteriner Udayana, 2016)
Dirofilaria immitis (D. immitis) as a causative agent of heartworm disease is not only caused problems in animals but also zoonoses.  For diagnosis of dirofilariasis (disease caused by D. immitis) serologically is needed anti- D. immitis antibodies.  The objective of this study was to produce antibodies against excretory-secretory antigens produced by male and female worms for developing the diagnosis of dirofilariasis based on the antigens detection.  Base on this study can be concluded that male excretory-secretory antigens (MES), female excretory-secretory antigens (FES), and MES+FES can stimulate BALB/c mouse to produce polyclonal antibodies in the same pattern. Antibodies have been produced at day 21 and the peak titter was at day 35 after first immunization.
Keywords: Dirofilaria immitis; antibodi; antigen ekskretori-sekretori; antibodies; excretory-secretory antigens